2022
DOI: 10.1038/s41598-022-08115-1
|View full text |Cite
|
Sign up to set email alerts
|

Simulating dynamic facial expressions of pain from visuo-haptic interactions with a robotic patient

Abstract: Medical training simulators can provide a safe and controlled environment for medical students to practice their physical examination skills. An important source of information for physicians is the visual feedback of involuntary pain facial expressions in response to physical palpation on an affected area of a patient. However, most existing robotic medical training simulators that can capture physical examination behaviours in real-time cannot display facial expressions and comprise a limited range of patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As an initial test, we synthesized one face identity (a white male) even though the Morphface can render many other face identities of different ethnicities in the face mediated approach. Recent studies 51 , 52 have reported the variability of interpretation of pain facial expressions. Thus, face identity feature variations (e.g., sex, ethnicity, age) in the MophFace could provide the participant/observer with more information about pain experience and this will be examined in future work.…”
Section: Discussionmentioning
confidence: 99%
“…As an initial test, we synthesized one face identity (a white male) even though the Morphface can render many other face identities of different ethnicities in the face mediated approach. Recent studies 51 , 52 have reported the variability of interpretation of pain facial expressions. Thus, face identity feature variations (e.g., sex, ethnicity, age) in the MophFace could provide the participant/observer with more information about pain experience and this will be examined in future work.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, virtual and/or physical training simulators have been proposed to address the issues related to SPs. Medical training simulators like the robopatient (Lalitharatne et al, 2021;Lalitharatne et al, 2022;Tan et al, 2022) enable medical students to practice hands-on medical skills on demand, as opposed to on limited resources of professional actors or real patients (Walker et al, 1990). These technologies have been proven to lead to better development of the required skills by medical students (Schubart et al, 2012).…”
Section: Introductionmentioning
confidence: 99%